2021
DOI: 10.4103/jfmpc.jfmpc_1749_20
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of overweight and obesity and their associated factors among health sciences college students, Saudi Arabia

Abstract: Context: The healthcare sciences college students have a lifestyle with low physical activity and disordered eating habits, which exposes them to a higher risk of obesity. Health science college students were the target group of particular interest in this study as they are future physicians. If they are overweight or obese, they will carry the wrong impression to the general population. Aim: To assess the prevalence of overweight and obesity among healthcare science co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
8
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 36 publications
3
8
1
Order By: Relevance
“…This prevalence was significantly lower than that found in a study carried out in the northern border university (Mehmood et al, 2016). However, it is in concurrence with the reported study in KSU (Saeed et al, 2017) and slightly higher than that of the reported finding in Dar Al-Uloom study (Makkawy et al, 2021). One surprising finding was revealing the significant disparity between obese female and male students.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…This prevalence was significantly lower than that found in a study carried out in the northern border university (Mehmood et al, 2016). However, it is in concurrence with the reported study in KSU (Saeed et al, 2017) and slightly higher than that of the reported finding in Dar Al-Uloom study (Makkawy et al, 2021). One surprising finding was revealing the significant disparity between obese female and male students.…”
Section: Discussionsupporting
confidence: 83%
“…A study of Shaqra University's medical students revealed that 19.3% of them were obese and 25.4% were overweight (Aqeel et al, 2020). In a survey of medical students at Dar Al Uloom University in Riyadh, it was discovered that overweight students made up 23.7% of the participants and obese students made up 11% of the participants (Makkawy et al, 2021). A study conducted on the health colleges of King Saud University, Riyadh it was found that 13.7% of students were obese (Saeed et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of obesity and overweight status in Saudi Arabia is worrying, and it has risen rapidly in recent decades to become one of the world's highest rates of overweight status and obesity prevalence (DeNicola et al 2015;Habbab and Bhutta 2020). In a recent cross-sectional study conducted among medical and dentistry students (mean age 22 year) in Saudi Arabia, 23.7 % of those who took part were overweight, and 11% were obese (Makkawy et al 2021). However, the study used BMI as an instrument to classify obesity.…”
Section: Discussionmentioning
confidence: 99%
“…Stress affects students’ coping behaviors, such as eating habits, smoking, and substance abuse [ 9 , 12 ]. This might reflect the high prevalence of obesity reported in health colleges, which was associated with lower academic performance and higher stress levels [ 13 , 14 ]. Stress was also linked to blood type and comorbidities such as insulin resistance and hypertension [ 15 ].…”
Section: Introductionmentioning
confidence: 99%